Role of the NLRP3 Inflammasome in Preeclampsia - Shirasuna, Koumei; Karasawa, Tadayoshi; Takahashi, Masafumi (Frontiers in Endocrinology, 2020)
Reproduction involves tightly regulated series of events and the immune system is involved in an array of reproductive processes. Disruption of well-controlled immune functions leads to infertility, placental inflammation, and numerous pregnancy complications, including preeclampsia (PE). Inflammasomes are involved in the process of pathogen clearance and sterile inflammation. They are large multi-protein complexes that are located in the cytosol and play key roles in the production of the pivotal inflammatory cytokines, interleukin (IL)-1β and IL-18, and pyroptosis. The nucleotide-binding oligomerization domain, leucine-rich repeat-, and pyrin domain-containing 3 (NLRP3) inflammasome is a key mediator of sterile inflammation induced by various types of damage-associated molecular patterns (DAMPs). Recent evidence indicates that the NLRP3 inflammasome is involved in pregnancy dysfunction, including PE. Many DAMPs (uric acid, palmitic acid, high-mobility group box 1, advanced glycation end products, extracellular vesicles, cell-free DNA, and free fatty acids) are increased and associated with pregnancy complications, especially PE. This review focuses on the role of the NLRP3 inflammasome in the pathophysiology of PE.